Answer:
See explanations
Step-by-step explanation:
(a) Assuming R3 is set such that the bridge is balanced (i.e. Vab = 0), derive an analytical expression for
Rx in terms of R1, R2 and R3.
Since Vab = 0, Va and Vb must be equal. Using voltage divider relations gives:
Va = Vin µ
R3
R1 + R3
¶
and Vb = Vin µ
Rx
R2 + Rx
¶
Setting these equal to each other and simplifying, we get
R1
R3
=
R2
Rx
, or Rx =
R2R3
R1
.
(b) . . . suppose that Rx varies in a way that makes Vab nonzero. Derive an expression for the dependence
of Vab on Rx.
Vab = Vb−Va = Vin µ
Rx
R2 + Rx
−
R3
R1 + R3
¶
or, if you prefer: Vab = Vin ·
R1Rx − R2R3
(R1 + R3)(R2 + Rx)